Role of Ixodes Pavlovskyi (Acari, Ixodidae) in Borreliosis Epizootic Process at the Island Russky - A. Ya. Nikitin; Yu. V. Sabitova; V. A. Rar; I. М. Morozov; N. S. Gordeiko; A. V. Allenov; G. B. Kaverina; I. V. Babkin; N. V. Tikunova; E. I. Andaev (Проблемы особо опасных инфекций, 2021)
The incidence of Ixodes tick-borne borreliosis (ITBB) at the Island Russky (Primorsk Territory) is higher than at the mainland. There is a bidominant structure of the tick population with mass occurrence of Ixodes persulcatus and I. pavlovskyi at the island. Due to the higher infectivity and aggressiveness of I. persulcatus, it is suggested that it plays a key role in high activity of the ITBB focus at the island.The aim of the study: to characterize the role of I. pavlovskyi in the borreliosis epizootic process based on the study of the structure of the borrelia genotype complex isolated from Ixodes ticks at the Island Russky.Materials and methods. The ticks were collected from vegetation at three sites. Ixodide species were determined morphologically and using PCR for mitochondrial gene cox1 and nuclear multicopy locus ITS2. Infection of 233 ticks was analyzed with the species identification confirmed by all methods. Borrelia genospecies were determined by multiplex two-round PCR with the primers specific to the gene fragments 5S and 23S rRNA of Borrelia burgdorferi sensu lato complex.Results and discussion. Coexistence of I. persulcatus and I. pavlovskyi at the island was confirmed, with different ratios in space and a gradual increase in the proportion of the latter species. The circulation of three etiological agents of ITBB: Borrelia garinii (predominantly in I. pavlovskyi), B. bavariensis and B. afzelii (in I. persulcatus) was identified. Thus, an active natural focus of ITBB has formed at the island, probably including two uninsulated chains of borrelia circulation. One chain combines I. persulcatus and small and large mammals as the tick feeders. The second – I. pavlovskyi that can feed on mammals and birds. Due to the spatial variability of the ixodide population structure at different sections of the island, the ratio of the circulating borrelia species can change, and this species becomes the main vector of the pathogenic agents in areas of I. pavlovskyi absolute dominance.